Rewilding. - Pettorelli, Nathalie; Durant, Sarah M.; du Toit, Johan T. (Cambridge : Cambridge University Press, 2019)
Smithson, Robert
ecology, rewilding, economic and sociopolitical realities of rewilding as a tool, wilderness, earth art
boek